(untitled) (PRÁXIS EM SAÚDE, 2026)
The present study describes the clinical and organizational impacts of the Center for Inclusive Education and Multidisciplinary Care (NEIAM), as an integral part of the Porto Trombetas Hospital, located in Western Pará, during the period from 2024 to 2025. The Amazonian model of multiprofessional rehabilitation is based on interdisciplinarity, daily integration among the fields of psychology, speech therapy, and occupational therapy, as well as systematic case discussions, fostering a practice centered on autonomy, independence, and family protagonism. On average, 85 patients were assisted monthly, including children and adolescents with atypical development, such as Autism Spectrum Disorder (ASD), Attention Deficit Hyperactivity Disorder (ADHD), and Intellectual Developmental Disorder (IDD). They were followed by up to three specialties, with significant results and a substantial reduction in the waiting list due to the agility of the screening process and joint assessment. The experience confirms the importance of integrated models aligned with the guidelines of the World Health Organization (WHO), which advocates family-centered rehabilitation and shared responsibility in the therapeutic process. It is concluded that the NEIAM/HPTR model represents a sustainable, replicable, and humanized practice of multiprofessional rehabilitation in the Amazon.